AN ASSESSMENT OF UKRAINE’S INVESTMENT POTENTIAL IN TODAY’S REALITIES - Koldovskyi, Artem; Tarchynets, Oleksii (Socio-economic relations in the digital society, 2023)
The article addresses the issues related to the essential interpretation of the term "investment potential," its assessment in the current realities of Ukraine, and understanding of its role in crisis management of the national economy in modern conditions. The aim of the article is to identify investment potential as an economic category in the context of crisis management of the country’s economy and determine its current state in Ukraine. An analysis of theoretical approaches to defining the concept of investment potential has been conducted, and they have been categorized into resource, probabilistic, market, capacity, structural, and performance directions. The definition of crisis management of the national economy is characterized, attempting to determine the role of the country’s investment potential in such management. An analysis and assessment of the dynamics of foreign direct investments in Ukraine from 2002 to 2022 have been carried out, revealing that their total volume during the war year decreased by almost five times, negatively impacting the country’s economy. The research emphasizes the necessity for Ukraine to enhance its investment potential to finance the needs of recovery and stabilization of the economic situation, both in the post-war period and the current stage, considering the challenges of digitization. The article argues that due to russia’s military aggression and the prolonged war, Ukraine needs to explore new solutions to bring the national economy out of a crisis state and overcome the destructive consequences of warfare through digital solutions. This is achievable by boosting the country’s investment potential, especially considering the insufficient domestic resources.